Latino Immigrants’ Biological Parents’ Histories Of Substance Use Problems In Their Country Of Origin Predict Their Pre- And Post-Immigration Alcohol Use Problems - Blackson, Timothy C. (Subst Abus, 2014)
BACKGROUND: No studies to date have assessed whether recent young adult (ages 18–34) Latino immigrants’ biological parents’ histories of substance use problems (BPHSUP) in their country of origin predict their alcohol use problems at pre- and post-immigration to the United States (U.S.). METHODS: BPHSUP in their country of origin was assessed via interviews conducted by bilingual Latino researchers with recent Latino immigrants primarily from Cuba, Central and South America recruited through respondent driven sampling at the time of their immigration to southeastern U.S. Three-waves of data were collected to document Latino immigrants’ severity of alcohol use problems at pre-immigration and two annual post-immigration follow-up assessments. BPHSUP +/− status was used as a predictor of Latinos’ (N=452; 45.8% female, 54.2% male) Alcohol Use Disorders Identification Test (AUDIT) scores at pre- and post-immigration with age, education and income as covariates as wells as odds ratios for AUDIT classifications of hazardous use, harmful use and dependence. RESULTS: BPHSUP+ status predicted Latino immigrants’ higher AUDIT scores pre- and post-immigration by gender (p<.01) compared to Latino immigrants of BPHSUP− status controlling for age, education and income. BPHSUP+ status predicted odds ratios of 3.45 and 2.91 for alcohol dependence AUDIT classification for men and women respectively (T3). CONCLUSIONS: This study documents that BPHSUP +/− status in their country of origin predict their young adult Latino offspring’s severity of alcohol use problems pre-and post-immigration. These results may inform (1) community-based health care providers to screen recent young adult Latino immigrants for their BPHSUP+/− status and severity of alcohol use problems to redirect trajectories away from alcohol use disorders toward more normative post-immigration outcomes through culturally relevant prevention services and (2) future research advantages of differential susceptibility theory. Implications for future research and the need for replication studies in other geographic regions of the U.S. are discussed.